Waste farm: a productive landscape for integrated waste management - Mashazhu, Mabasa (School of Architecture, Planning and Geomatics, 2018)
In 2010 the city of Cape Town partnered with the Department of Environmental Affairs to initiate a project to investigate and evaluate the possible re-opening and licensing of Historic and Old landfill sites. The project to reassess these landfill sites is due to the fact that the three main operating landfill sites in Cape Town are nearing capacity. This calls for the city to re-imagine its waste management infrastructure. Meanwhile, within the urban areas of Cape Town, there exists a network and constellations of informal waste pickers working in conjunction with buy-back centres and recyclers to form an economically, environmentally and socially sustainable solution that diverts volumes of recyclable waste from landfills. These informal waste pickers contribute to filling in a gap within the formal recycling system but there is no infrastructure supporting these individuals on whom the formal recycling industry depends on. Most of the waste pickers sleep 'on the streets' with little access to amenities such as water, toilets and washing facilities. The spaces they occupy/sleep make it hard to store their pickings and hence they are forced to sell as soon as they collect. It also forces them to make multiple trips to the buy-back centres whom they are always at the mercy of, particularly when the ever changing price of recyclable waste is low. This project aims at creating a productive landscape that uses waste as a vehicle to enhance the livelihoods of informal waste pickers and encourage local communities to see the economic and environmental value of recycling waste. By providing secure storage and sorting, safe/hygienic sleeping and cleaning spaces coupled with social and productive areas; the project seeks to unlock the potential of recycling using a suitable architectural intervention that is self-sustaining.